Impaired Verb-Related Morphosyntactic Production in Multiple Sclerosis: Evidence From Greek - Fyndanis, Valantis; Messinis, Lambros; Nasios, Grigorios; Dardiotis, Efthimios; Martzoukou, Maria; Pitopoulou, Maria; Ntoskou, Aikaterini; Malefaki, Sonia (Frontiers in Psychology, 2020)
Background: A recent systematic review found that language deficits are not very common in individuals with multiple sclerosis (MS). However, there are significant gaps in our knowledge about language abilities in MS. For instance, morphosyntactic production has not been explored adequately thus far. This study investigated verb-related morphosyntactic production in MS focusing on Greek, a morphologically rich language. Methods: A sentence completion task tapping into the production of subject-verb Agreement, Time Reference/Tense and grammatical Aspect was administered to 39 Greek-speaking individuals with MS (25 individuals with relapsing-remitting MS (RRMS group) and 14 individuals with secondary progressive MS (SPMS group)). The task included only regular verbs. Generalized linear mixed-effects models were used to investigate the ability of individuals with MS to produce the above mentioned morphosyntactic categories. Results: Overall, the RRMS and SPMS groups performed significantly worse than their matched control groups. Moreover, all four groups performed significantly worse on grammatical Aspect than on subject-verb Agreement and Time Reference. The difference between subject-verb Agreement and Time Reference was not significant in any of the four groups. The overall performances of the RRMS and SPMS groups did not differ significantly. Conclusion: Individuals with MS are impaired in verb-related morphosyntactic production. Moreover, the pattern of performance of individuals with MS is identical to that exhibited by neurologically healthy individuals. Thus, the production performance of individuals with MS on verb inflection differs from that of healthy controls quantitatively but not qualitatively.